A silicate zeolite molecular sieve ZMQ-1 and its use

By designing bistricyclohexyl/phenyl quaternary phosphorus cations as organic structure guides, a new aluminosilicate zeolite molecular sieve ZMQ-1 with a three-dimensional open framework structure was solved, and the pore size of the existing molecular sieve material remains in the micropore range and The problem of easy structure collapse has achieved ultra-large microporous molecular sieve with high heat and hydrothermal stability.

CN118515294BActive Publication Date: 2025-02-11QINGDAO INST OF BIOENERGY & BIOPROCESS TECH CHINESE ACADEMY OF SCI

Patent Information

Application Number
CN202410606237.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2023-05-31
Filing Date
2024-05-16
Publication Date
2025-02-11
Estimated Expiration
2044-05-16

AI Technical Summary

Technical Problem

The existing molecular sieve materials stay in the micropore category in pore size, and the structure is prone to collapse after the organic structure guide agent is removed, limiting its application range.

Method used

Bitricyclohexyl/phenyl quaternary phosphorus cation was designed as an organic structure guide agent, and a new aluminosilicate zeolite molecular sieve with a three-dimensional open framework structure was synthesized by hydrothermal crystallization method.

Benefits of technology

A three-dimensional pore system composed of ultra-large micropores and medium micropores is realized, with high thermal and hydrothermal stability, expanding the application range of molecular sieves.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118515294B_ABST
    Figure CN118515294B_ABST
Patent Text Reader

Abstract

The present invention relates to molecular sieves, in particular to a novel silicate zeolite molecular sieve ZMQ-1, and a preparation method and use thereof. The anhydrous chemical composition of the silicate zeolite molecular sieve precursor is SiO2·1 / xXO 1.5 mMO 0.5 ·qQ, where X is a framework trivalent element, Si / X molar ratio x≥5, M is a framework balancing cation, M / Si molar ratio 0≤m≤1, Q is a diquaternary ammonium or diquaternary phosphorus organic structure directing agent, Q / Si molar ratio q≥0.01. The anhydrous chemical composition of silicate zeolite molecular sieve is SiO2·1 / xXO 1.5 mMO 0.5 , wherein X is a framework trivalent element, Si / X molar ratio x≥5, M is a framework balanced cation, and M / Si molar ratio 0≤m≤1. The molecular sieve of the present invention can be further applied to energy storage, sensing, loading, adsorption, separation or catalysis processes due to its novel topological structure, unique pore system, and high thermal and hydrothermal stability, and may exhibit unique properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a molecular sieve, in particular to a novel silicate zeolite molecular sieve ZMQ-1, and a preparation method and application thereof. Background Art

[0002] Zeolite molecular sieve (hereinafter referred to as molecular sieve) is a very important type of inorganic microporous material. For half a century, molecular sieve has been widely used in oil processing, petrochemical industry and environmental chemical industry as catalysis, adsorption separation and ion exchange materials. According to the number of pore rings, molecular sieve materials can be divided into small pore, medium pore, large pore and ultra-large pore molecular sieves, corresponding to the window ring numbers of 8-membered rings and below, 10-membered rings and below, 12-membered rings and below and greater than 13-membered rings and above. So far, there are 260 types of molecular sieve structures recognized and accepted by the International Molecular Sieve Association (official website: https: / / asia.iza-structure.org / IZA-SC / ftc_table.php), each structure is represented by three capital letters, but there are less than 20 molecular sieves that have been truly industrialized, such as A-type, X-type and Y-type, mordenite, ZSM-5, ZSM-11, MCM-22, L-type, β-type, erionite, RHO, CHA, AEL type and TS-1, as well as SAPO-34, SAPO-11, SAPO-31, etc. In view of this, the development of molecular sieve materials with new structures and new properties has always been an important research direction in this field, which will effectively expand the application scope of molecular sieves and meet the growing needs of related industrial processes.

[0003] At present, the synthetic exploration method for new molecular sieves is still mainly based on trial and error or empirical method. The disadvantages of this method are that it is time-consuming, labor-intensive and not easy to obtain the desired target product. In addition, a large amount of waste will be generated in the process, which is a non-green and environmentally friendly molecular sieve synthesis method. In the 1960s, researchers introduced organic species into the molecular sieve synthesis process, and many new structures of high-silicon molecular sieves were synthesized. For example, tetraethylammonium, tetrapropylammonium and tetrabutylammonium cations were used as organic additives to successfully synthesize β, ZSM-5 and ZSM-11 molecular sieves. These organic species are usually used together with alkali metal cations, and because they have a filling effect on the molecular sieve pores, they were initially called "templates". However, with the in-depth study of the molecular sieve synthesis mechanism, it was found that many organic species do not have a strict matching relationship with the molecular sieve pore size or structure, and in many cases, one organic species can be synthesized to obtain a variety of different molecular sieve structures. Therefore, researchers named them "organic structure directing agents" (OSDAs), which is also a definition generally accepted in the field of molecular sieve synthesis. The effect they produce is called "structure directing effect" (ME Davis and RF Lobo, Chem. Mater., 1992, 4, 756-768). The proposal of "structure directing effect" provides methodological guidance for the synthesis of molecular sieves, making the synthesis process more purposeful.

[0004] According to the different types of organic cations, organic structure-directing agents can be divided into quaternary ammonium cations, imidazolyl cations, quaternary phosphonium cations, sulfonium cations, proton sponges, metal complexes and neutral amines, among which quaternary ammonium and quaternary phosphonium cations are the most mature and widely used. Compared with quaternary ammonium cations, quaternary phosphonium cations have the following advantages: (1) the phosphorus atom is larger than the nitrogen atom, so it is easier to connect larger substituent groups; (2) quaternary phosphonium cations have higher thermal stability and can exist stably in an alkaline system at 190°C, while most quaternary ammonium cations will decompose and lose their structure-directing agent function. Therefore, in recent years, phosphorus-containing organic structure-directing agents have been widely used and developed, and several new structure molecular sieves have been synthesized (CN114538466A and CN115611293A), showing great potential in the development of new structure molecular sieves, which deserve further exploration and research.

[0005] In addition, the introduction of other inorganic species can also provide additional structural guidance. They can jointly guide the formation of molecular sieves with specific structures. Molecular sieves are microporous structural materials formed by alternating connections of TO4 tetrahedrons. Other elements, such as B, Al, Be, Mg, Ga, Ge, Zn and Co, can enter the molecular sieve framework through isomorphous substitution. The introduction of heteroatoms will also produce some unique chemical and physical properties, such as catalytic performance, selective adsorption or magnetic properties. In addition, heteroatoms will significantly affect the formation process of molecular sieves. For example, Ge, B, Ga, Zn and Be are conducive to the formation of specific structural units (such as 4-membered rings, 3-membered rings, double 4-membered rings, double 3-membered rings and spiro 5-membered rings, etc.), because their suitable TO bonds and TOT bond angles can stabilize these structural units.

[0006] In recent years, dozens of new molecular sieves have been synthesized based on the strategy of organic structure directing agent design and heteroatom introduction. The Avelino Corma research group in Spain has developed a variety of new molecular sieves named ITQ-n (Molineret al, Angew. Chem. Int. Ed. 2013, 52, 13880-13889 and Li et al, Chem. Soc. Rev., 2015, 44, 7112-7127). The pore sizes of these molecular sieves range from small pores to ultra-large pores, greatly expanding the types of molecular sieve structures. However, most of these new molecular sieves contain germanium. After removing the organic structure directing agent and exposing it to air, the framework germanium will hydrolyze, eventually leading to the collapse of the framework, which greatly limits its practical application. The Sukbong Hong research group in South Korea found that the weak interaction between organic cations, inorganic cations and aluminum species can also lead to the generation of molecular sieves with specific structures. They fixed the type of organic cations and introduced two inorganic cations (Na + and Cs + ), forming a mismatch in charge density of the synthesis system, synthesizing a structurally stable macroporous SBT aluminosilicate molecular sieve, solving the problem of structural collapse after the removal of the organic structure directing agent of the molecular sieve (Lee et al., 2021, Science 373, 104-107 and Lee et al., J. Am. Chem. Soc. 2022, 144, 18700-18709). However, this method involves many modulation factors, and the target molecular sieve can only be obtained within a narrow gel ratio range, which will affect the repeatability of the synthesis results to a certain extent. In addition, the synthesized molecular sieve has a low silicon-aluminum ratio, that is, a high aluminum content, which reduces its hydrothermal stability.

[0007] In summary, although zeolite molecular sieves or molecular sieve materials with various topological structures have been obtained, the pore size remains in the micropore range, and there is still no report of zeolite molecular sieves with stable structure and intrinsic mesopores. In view of the new needs of processes such as adsorption separation and catalytic conversion of macromolecules, it is urgent to develop new thermally and hydrothermally stable crystalline molecular sieve materials. Summary of the invention

[0008] The present invention aims to provide a novel silicate zeolite molecular sieve (ZMQ-1), a preparation method and application thereof.

[0009] A silicate zeolite molecular sieve precursor, the anhydrous chemical composition of the silicate zeolite molecular sieve precursor is SiO2·1 / xXO 1.5 mMO 0.5 qQ, wherein X is a framework trivalent element, Si / X molar ratio x≥5, M is a framework balancing cation, M / Si molar ratio 0≤m≤1, Q is a diquaternary ammonium or diquaternary phosphorus organic structure directing agent, Q / Si molar ratio q≥0.01.

[0010] The X-ray diffraction characteristics of the silicate zeolite molecular sieve precursor powder are as follows:

[0011]

[0012]

[0013] In the data of this application form, the relative intensity of diffraction peaks is defined as shown in the following table.

[0014] <![CDATA[100I / I0]]> Relative Strength <10 w(weak peak) 10-20 mw (medium to weak peak) 20-40 m(medium peak) 40-70 s(strong peak) >70 vs (very strong peak)

[0015] A new type of silicate zeolite molecular sieve, the anhydrous chemical composition of silicate zeolite molecular sieve is SiO2·1 / xXO 1.5 mMO 0.5 , wherein X is a framework trivalent element, the Si / X molar ratio x≥5, M is a framework balancing cation, and the M / Si molar ratio 0≤m≤1.

[0016] The novel silicate zeolite molecular sieve contains a three-dimensional pore system consisting of 28×10×10 rings, wherein the size of the 28-membered ring is The sizes of the 10-membered ring are and

[0017] The silicate molecular sieve is a novel topological structure of ultra-large pore molecular sieve, the largest pore of which is composed of 28-membered rings and has a size of It exceeds the micropore range defined by the International Organization for Standardization (less than 2nm). More importantly, the ZMQ-1 molecular sieve can be adjusted within the composition range of low silicon, high silicon or pure silicon.

[0018] The novel silicate zeolite molecular sieve has the powder X-ray diffraction characteristics shown in the following table:

[0019]

[0020]

[0021] The crystal structure of the molecular formula is an orthorhombic system, the space group is Cmmm (No.65), and the unit cell parameters are: and And, it has the topological characteristics shown in the following table:

[0022]

[0023]

[0024] The novel silicate zeolite molecular sieve is obtained by calcining the novel silicate zeolite molecular sieve precursor.

[0025] The framework trivalent element X is selected from at least one of boron, aluminum, gallium, indium, iron and chromium; the framework balanced cation M is selected from at least one of hydrogen ion, ammonium ion, lithium ion, sodium ion, potassium ion, rubidium ion, cesium ion, magnesium ion, calcium ion, strontium ion and barium ion; the molecular sieve contains a non-silicon tetravalent framework element (Y) with a mass greater than 0 and less than or equal to 10w%, wherein Y is selected from at least one of germanium, tin, titanium, zirconium and hafnium; silicon in the precursor or molecular sieve can be partially replaced by at least one of germanium, tin, titanium, zirconium and hafnium; other framework divalent elements (Z) can be introduced into the molecular sieve, wherein Z is selected from at least one of zinc, beryllium, copper, cobalt, iron, manganese, chromium, molybdenum and tungsten, and the molar ratio of divalent elements to silicon is greater than 0 and less than or equal to 0.1.

[0026] A method for preparing the novel silicate zeolite molecular sieve:

[0027] A framework balanced cationic compound, a silicon source, a framework trivalent element X source, an organic structure directing agent and a reagent are mixed to obtain a synthetic gel; the synthetic gel is then aged and hydrothermally crystallized, and the crystallized product is roasted to remove the organic structure directing agent; wherein the molar ratio of the synthetic gel after aging is SiO2:mM2O:xX2O3:qQ(OH)2:hH2O, wherein M is a framework balanced cation, X is a framework trivalent element, and Q is a cationic group of the organic structure directing agent, and the value ranges of m, x, q and h are: m=0-1, x=0-0.5, q=0.1-1, and h=3-100;

[0028] The reagent is water and / or a fluorine-containing mineralizer;

[0029] The organic structure directing agent has the following configuration:

[0030]

[0031] Wherein, Q can be the same or different and selected from nitrogen or phosphorus, R1, R2, R3, R4, R5, R6 can be the same or different and selected from cyclohexyl or phenyl, R7 and R8 can be the same or different and selected from H or methyl, and n is 0-8, preferably 3-5.

[0032] Further, the preparation method is:

[0033] (1) Weighing a framework balanced cationic compound, a silicon source, a framework trivalent element X source, an organic structure directing agent and a reagent according to stoichiometric quantities, adding them into an open container in the order of liquid phase first and solid phase second, and mixing them evenly under magnetic stirring to obtain an initial synthetic gel.

[0034] (2) Stirring and aging the synthetic gel at room temperature for 12-24 hours, and then aging it in an oven at 60-100°C for 2-6 hours, while removing excess solvents and reagents. The final synthetic gel molar ratio is SiO2:mM2O:xX2O3:qQ(OH)2:hH2O, wherein M is a framework balancing cation, X is a framework trivalent element, and Q is a cationic group of an organic structure directing agent. The value ranges of m, x, q and h are: m=0-1, x=0-0.5, q=0.1-1, h=3-100. The preferred range is: m=0-0.15x=0-0.1, q=0.1-0.3, h=5-50.

[0035] (3) The synthetic gel is transferred to a polytetrafluoroethylene liner, placed in a stainless steel synthesis kettle, sealed, and finally placed in an oven for crystallization. The crystallization temperature is 50-250°C, preferably 100-200°C; the crystallization time is 1-30 days, preferably 5-15 days; the crystallization method is static or / and rotational crystallization.

[0036] (4) After washing and drying, the crystallization reaction product is calcined at 500-1000°C in air or / and inert atmosphere for 3-24 hours to remove the organic structure directing agent and obtain aluminosilicate zeolite molecular sieve. The calcination temperature is preferably 550-750°C and the calcination time is preferably 6-12 hours.

[0037] In addition, during the synthesis of the zeolite molecular sieve, seed crystals may be further added during the gel synthesis process. The seed crystals are the zeolite molecular sieve synthesized in the above step (3), and are in the form of a molecular sieve before or after calcination.

[0038] In the above synthesis process, the source of the framework trivalent element X is selected from at least one of a boron source, an aluminum source, a gallium source, an indium source, an iron source and a chromium source; the boron source is selected from at least one of boric acid, sodium tetraborate, amorphous boron oxide, potassium borate, sodium metaborate, ammonium tetraborate and an organic boron ester; the aluminum source is selected from at least one of aluminum sulfate, sodium aluminate, aluminum nitrate, aluminum chloride, pseudo-boehmite, aluminum oxide, aluminum hydroxide, silica-aluminum zeolite molecular sieve, aluminum carbonate, elemental aluminum, aluminum isopropoxide and aluminum acetate; the gallium, indium and chromium sources can be selected from at least one of gallium oxide, gallium nitrate, indium oxide, indium nitrate, chromium chloride and chromium nitrate, etc.; the iron source is selected from at least one of ferric sulfate, ferric nitrate, ferric halide, ferrocene and ferric citrate The framework balanced cationic compound is selected from at least one of hydroxides (such as lithium hydroxide and sodium hydroxide) and halides (such as lithium chloride and sodium chloride); the silicon source is selected from one or more of tetraethyl orthosilicate, silica sol, fumed silica, silicic acid and water glass; a non-silicon tetravalent framework element source (Y) may be added to the silicon source in an amount greater than 0 and less than or equal to 10w% of the mass of the silicon source, wherein Y is selected from at least one of germanium, tin, titanium, zirconium and hafnium; other framework divalent elements (Z) may be introduced into the molecular sieve, wherein Z is selected from at least one of zinc, beryllium, copper, cobalt, iron, manganese, chromium, molybdenum and tungsten, and the molar ratio of the divalent element to silicon is greater than 0 and less than or equal to 0.1.

[0039] The fluorine-containing mineralizer is NH4F and / or HF.

[0040] A molecular sieve composition contains the silicate zeolite molecular sieve precursor and / or the silicate zeolite molecular sieve.

[0041] An application of the novel silicate zeolite molecular sieve, the application of the silicate zeolite molecular sieve or the molecular sieve composition as an energy storage material, chemical sensing material, carrier, adsorbent, separation agent or catalyst.

[0042] Furthermore, the silicate zeolite molecular sieve or the molecular sieve composition is used as an energy storage material, a chemical sensing material, a carrier, an adsorption separation agent or a catalyst.

[0043] Among them, in terms of energy storage material applications, it can be used as a storage material for hydrogen and hydrogen mixed media (such as hydrogen-methane, hydrogen-ethane and hydrogen-propane systems).

[0044] Among them, in the application of chemical sensing materials, it can be used to monitor light hydrocarbons, alkaline molecules, carbon dioxide, sulfide gas and humidity, etc.

[0045] Among them, in terms of carrier application, it can be used to carry metals, non-metals and bio-enzymes to prepare catalysts, and to carry drugs for imaging and treatment.

[0046] Among them, in terms of adsorption separation agent application, it can be used as a desiccant to remove water, adsorb volatile organic compounds (VOCs), treat wastewater containing dye macromolecules, and separate sugar and protein small molecules. More specifically, due to its regular ultra-large micropore channels, it can be used as a high-performance liquid chromatography column filler.

[0047] Among them, in terms of catalyst application, it can be used for hydrogenation or direct catalytic cracking of vacuum gas oil (VGO) to produce gasoline, diesel and other chemicals, hydrogenation or direct catalytic cracking of vacuum residue to produce oil products and olefins and other chemicals, other fossil energy and renewable energy conversion to produce high value-added chemicals, and isomerization, disproportionation and Friedel-Crafts alkylation reactions involving organic macromolecular substrates. More specifically, given its unique 10-membered ring micropores, the application of this molecular sieve in the cracking process of VGO and vacuum residue will be conducive to the production of low-carbon olefins, especially ethylene and propylene, which is of great significance for the upgrading and utilization of fossil energy in my country.

[0048] The advantages of the present invention are:

[0049] The present invention designs a bis(tricyclohexyl) / phenyl quaternary phosphonium cation as an organic structure directing agent to synthesize a novel aluminosilicate zeolite molecular sieve with a three-dimensional open skeleton structure, the zeolite molecular sieve has a unique powder X-ray diffraction peak, and furthermore, has a three-dimensional pore system consisting of one super-large micropore and two meso-micropores. In addition, the molecular sieve has high thermal and hydrothermal stability.

[0050] In view of its novel topological structure, unique pore system, high thermal and hydrothermal stability, the molecular sieve of the present invention can be further applied to adsorption, separation or catalysis processes involving macromolecules or related to diffusion limitation, and may exhibit unique properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0051] Figure 1 These are the powder X-ray diffraction spectra of the freshly synthesized zeolite molecular sieve precursor provided in Examples 3-5 of the present invention, and the zeolite molecular sieve ZMQ-1 calcined at 600° C. for 6 hours and 800° C. for 1 hour.

[0052] Figure 2 This is the powder X-ray diffraction spectrum of ZMQ-1 of the zeolite molecular sieve calcined at 600°C provided in Example 3-5 of the present invention after being treated with 50% water vapor at 600°C, 700°C and 800°C for 3 hours.

[0053] Figure 3 1 is the X-ray diffraction spectrum of the ZMQ-1 molecular sieves with different Ti contents synthesized in Examples 14 and 15 of the present invention.

[0054] Figure 4 It is the argon physical adsorption data of the calcined zeolite molecular sieve of the present invention.

[0055] Figure 5 It is the crystallographic pore size of the molecular sieve of the present invention.

[0056] Figure 6 These are scanning electron microscope and transmission electron microscope photographs of the sample calcined at 600° C. in Example 3 of the present invention.

[0057] Figure 7 These are scanning electron microscope and transmission electron microscope photographs of the sample calcined at 600° C. in Example 11 of the present invention.

[0058] Figure 8 The skeleton (A, B, DF) of the molecular sieve calcined at 600°C in Example 3 and the high-resolution transmission electron microscope atomic image (C). DETAILED DESCRIPTION

[0059] The specific implementation modes of the present invention are further described below in conjunction with examples. It should be noted that the specific implementation modes described here are only for illustrating and explaining the present invention, and are not limited to the present invention.

[0060] In Example 3-13, the powder X-ray diffraction data of the sample was analyzed using a Japanese Rigaku X-ray diffractometer, model LabView, with a CuKα X-ray source and a wavelength of The argon adsorption and desorption analysis of the samples was performed using an American Quantachrome adsorption instrument, model Autosorb iQ. The elemental analysis of the samples was performed using an American Agilent (formerly Varian) ICP-730ES inductively coupled plasma emission spectrometer. The scanning electron microscope and transmission electron microscope images of the samples were collected from a Japanese Hitachi cold field emission scanning electron microscope S-4800 and a Japanese electron high-resolution transmission electron microscope JEM-F200, respectively.

[0061] The synthesis method for preparing molecular sieves in the following examples is hydrothermal crystallization, and the organic structure directing agent used is a diquaternary ammonium / phosphonium cation of different lengths and structures, and the organic structure directing agent is selected from any one or more of the following table.

[0062] Table 1.

[0063]

[0064]

[0065]

[0066] Among the organic structure directing agents, any one or more of organic structure directing agents 3, 4, 9, and 10 are more preferred.

[0067] Example 1: Synthesis of organic structure directing agent

[0068] Take the synthesis of organic structure directing agent 4 as an example. Weigh 36.51g of tricyclohexylphosphine into a 500mL three-necked round-bottom flask, add 200mL of chloroform, stir magnetically to dissolve, and transfer to an ice bath. Under magnetic stirring, slowly drop 13.88g of 1,8-dibromooctane into the flask, and continue to stir the resulting mixture solution for 1 hour. Subsequently, it was refluxed and heated at 75°C for 3 days. After the resulting mixture was naturally cooled to room temperature, excess ethyl acetate was added to precipitate the product, filtered, washed with ethyl acetate, and the residual solvent was removed by rotary evaporation to obtain a final product of 39.16g with a yield of 94%. It was determined to be the target compound by liquid phase nuclear magnetic resonance and CHN elemental analysis.

[0069] In a plastic beaker, dissolve the organic structure directing agent powder in 200mL of deionized water, then pour in the pre-activated Zhengzhou Xidian ZXUR-90 strong base anion exchange resin, and stir magnetically for 12 hours. Filter, wash, recover the filtrate, and obtain a concentrated organic structure directing agent solution after rotary evaporation. Take a small amount of solution, dilute it to 50mL with water, take 1.00g of 0.1mol / L hydrochloric acid standard solution, add phenol as an indicator, and titrate with the diluted organic structure directing agent solution to determine that the final exchange degree is 95%.

[0070] Example 2: Synthesis of organic structure directing agent

[0071] Take the synthesis of organic structure directing agent 10 as an example. Weigh 36.51g of tricyclohexylphosphine into a 500mL three-necked round-bottom flask, add 200mL of chloroform, stir magnetically to dissolve, and transfer to an ice bath. Under magnetic stirring, slowly drop 15.31g of 1,8-dibromo-2,7-dimethyloctane into the flask, and continue to stir the resulting mixture solution for 1 hour. Subsequently, it was refluxed at 75°C for 3 days. After the resulting mixture was naturally cooled to room temperature, excess ethyl acetate was added to precipitate the product, filtered, washed with ethyl acetate, and the residual solvent was removed by rotary evaporation to obtain a final product of 40.99g with a yield of 95%. It was confirmed as the target compound by liquid phase nuclear magnetic resonance and CHN elemental analysis.

[0072] In a plastic beaker, dissolve the organic structure directing agent powder in 200mL of deionized water, then pour in the pre-activated Zhengzhou Xidian ZXUR-90 strong base anion exchange resin, and stir magnetically for 12 hours. Filter, wash, recover the filtrate, and obtain a concentrated organic structure directing agent solution after rotary evaporation. Take a small amount of solution, dilute it to 50mL with water, take 1.00g of 0.1mol / L hydrochloric acid standard solution, add phenol as an indicator, and titrate with the diluted organic structure directing agent solution to determine that the final exchange degree is 97%.

[0073] Meanwhile, according to the preparation process described in the above Example 1 or 2, other organic structure directing agents described in Table 1 can be obtained by replacing the phosphorus cation with an ammonium cation, or replacing the substituent group or methylene chain length connected to the phosphorus / ammonium cation.

[0074] Example 3: Synthesis of zeolite molecular sieve

[0075] The synthetic gel was prepared according to the molar ratio of SiO2:0.02Al2O3:0.25Q(OH)2:10H2O, and the specific steps were as follows: 6 mmol of the organic structure directing agent solution described in Example 1 was weighed, 0.21 g of aluminum isopropoxide was added, and magnetic stirring was performed for 1 hour, followed by the addition of 5.21 g of tetraethyl orthosilicate, and the resulting mixture was stirred at room temperature for 12 hours. The resulting transparent gel was placed in a vacuum oven and heated at 100°C for 3 hours to remove the solvent and excess water. The final synthetic gel was transferred to a 25 mL stainless steel synthesis kettle with a polytetrafluoroethylene liner and crystallized at 190°C for 10 days. The product was filtered and washed with 200 mL of water, 200 mL of ethanol, and 100 mL of acetone, and dried overnight to obtain a freshly synthesized zeolite molecular sieve precursor. Subsequently, the organic structure directing agent was removed by calcination at 600°C for 6 hours in a muffle furnace under a flowing air atmosphere. The product was identified as ZMQ-1 by powder X-ray diffraction, and the silicon-aluminum atomic ratio was 15.9 by ICP-OES elemental analysis.

[0076] Example 4: Calcination of Zeolite Molecular Sieve

[0077] The freshly synthesized zeolite molecular sieve precursor prepared in Example 3 was placed in a muffle furnace and calcined at 800° C. for 1 hour under a flowing air atmosphere to remove the organic structure directing agent. The product was determined to be ZMQ-1 by powder X-ray diffraction. Figure 1 shown.

[0078] Example 5: Hydrothermal treatment of zeolite molecular sieve

[0079] The sample calcined at 600°C in Example 3 was divided into three parts, and placed in fixed bed reactors respectively. Deionized water was introduced into the reactors through a peristaltic pump under nitrogen atmosphere, and the relative humidity was maintained at 50%. The samples were treated at 600°C, 700°C and 800°C for 3 hours respectively. After cooling naturally to room temperature, the treated zeolite molecular sieve was taken out, and the phase was still ZMQ-1 as determined by powder X-ray diffraction. Figure 2 shown.

[0080] Example 6: Zeolite Molecular Sieve Synthesis

[0081] The synthetic gel was prepared according to the molar ratio of SiO2: 0.01Al2O3: 0.25Q(OH)2: 10H2O, and the specific steps were as follows: 6 mmol of the organic structure directing agent solution described in Example 1 was weighed, 0.10 g of aluminum isopropoxide was added, and magnetic stirring was performed for 1 hour, followed by the addition of 5.21 g of tetraethyl orthosilicate, and the resulting mixture was stirred at room temperature for 12 hours. The resulting transparent gel was placed in a vacuum oven and heated at 100°C for 3 hours to remove the solvent and excess water. The final synthetic gel was transferred to a 25 mL stainless steel synthesis kettle with a polytetrafluoroethylene liner and crystallized at 190°C for 10 days. The product was filtered and washed with 200 mL of water, 200 mL of ethanol, and 100 mL of acetone, and dried overnight to obtain a freshly synthesized zeolite molecular sieve precursor. Subsequently, the organic structure directing agent was removed by calcination at 600°C for 6 hours in a muffle furnace under a flowing air atmosphere. The product was identified as ZMQ-1 by powder X-ray diffraction, and the silicon-aluminum atomic ratio was 35.2 by ICP-OES elemental analysis.

[0082] Example 7: Zeolite Molecular Sieve Synthesis

[0083] The synthetic gel was prepared according to the molar ratio of SiO2: 0.005Al2O3: 0.25Q(OH)2: 10H2O, and the specific steps were as follows: 6 mmol of the organic structure directing agent solution described in Example 1 was weighed, 0.05 g of aluminum isopropoxide was added, and magnetic stirring was performed for 1 hour, followed by the addition of 5.21 g of tetraethyl orthosilicate, and the resulting mixture was stirred at room temperature for 12 hours. The resulting transparent gel was placed in a vacuum oven and heated at 100°C for 3 hours to remove the solvent and excess water. The final synthetic gel was transferred to a 25 mL stainless steel synthesis kettle with a polytetrafluoroethylene liner and crystallized at 190°C for 10 days. The product was filtered and washed with 200 mL of water, 200 mL of ethanol, and 100 mL of acetone, and dried overnight to obtain a freshly synthesized zeolite molecular sieve precursor. Subsequently, the organic structure directing agent was removed by calcination at 600°C for 6 hours in a muffle furnace under a flowing air atmosphere. The product was identified as ZMQ-1 by powder X-ray diffraction, and the silicon-aluminum atomic ratio was determined to be 67.5 by ICP-OES elemental analysis.

[0084] Example 8: Zeolite Molecular Sieve Synthesis

[0085] The synthetic gel was prepared according to the molar ratio of SiO2: 0.02Al2O3: 0.25Q(OH)2: 10H2O, and the specific steps were as follows: 6 mmol of the organic structure directing agent solution described in Example 2 was weighed, 0.21 g of aluminum isopropoxide was added, magnetic stirring was performed for 1 hour, and then 5.21 g of tetraethyl orthosilicate was added. The resulting mixture was stirred at room temperature for 12 hours, and the resulting transparent gel was placed in a vacuum oven and heated at 100°C for 3 hours to remove the solvent and excess water. The final synthetic gel was transferred to a 25 mL stainless steel synthesis kettle with a polytetrafluoroethylene liner and crystallized at 190°C for 15 days. The product was filtered and washed with 200 mL of water, 200 mL of ethanol, and 100 mL of acetone, and dried overnight to obtain a fresh synthetic zeolite molecular sieve precursor. Subsequently, it was calcined at 600°C for 6 hours in a muffle furnace under a flowing air atmosphere to remove the organic structure directing agent. The product was identified as ZMQ-1 by powder X-ray diffraction, and the silicon-aluminum atomic ratio was 15.3 by ICP-OES elemental analysis.

[0086] Example 9: Zeolite Molecular Sieve Synthesis

[0087] The synthetic gel was prepared according to the molar ratio of SiO2: 0.02Na2O: 0.02Al2O3: 0.25Q(OH)2: 10H2O, and the specific steps were as follows: Weigh an appropriate amount of the organic structure directing agent solution described in Example 1, add 0.04g of sodium hydroxide and stir until dissolved, add 0.21g of aluminum isopropoxide, stir magnetically for 1 hour, then add 5.21g of tetraethyl orthosilicate, stir the resulting mixture at room temperature for 12 hours, and place the resulting transparent gel in a vacuum oven, heat at 100°C for 3 hours, and remove the solvent and excess water. The final synthetic gel was transferred to a 25mL stainless steel synthesis kettle with a polytetrafluoroethylene liner and crystallized at 190°C for 5 days. The product was filtered and washed with 200mL of water, 200mL of ethanol, and 100mL of acetone, and dried overnight to obtain a freshly synthesized zeolite molecular sieve. Subsequently, it was calcined at 600°C for 6 hours in a muffle furnace under a flowing air atmosphere to remove the organic structure directing agent. The product was identified as ZMQ-1 by powder X-ray diffraction, and the silicon-aluminum atomic ratio was 15.9 by ICP-OES elemental analysis.

[0088] Example 10: Synthesis of zeolite molecular sieve

[0089] The synthetic gel was prepared according to the molar ratio of SiO2: 0.02Na2O: 0.02Al2O3: 0.25Q(OH)2: 10H2O, and the specific steps were as follows: Weigh an appropriate amount of the organic structure directing agent solution described in Example 2, add 0.04g of sodium hydroxide and stir until dissolved, add 0.21g of aluminum isopropoxide, stir magnetically for 1 hour, then add 5.21g of tetraethyl orthosilicate, stir the resulting mixture at room temperature for 12 hours, and place the resulting transparent gel in a vacuum oven, heat at 100°C for 3 hours, and remove the solvent and excess water. The final synthetic gel was transferred to a 25mL stainless steel synthesis kettle with a polytetrafluoroethylene liner and crystallized at 190°C for 5 days. The product was filtered and washed with 200mL of water, 200mL of ethanol, and 100mL of acetone, and dried overnight to obtain a freshly synthesized zeolite molecular sieve. Subsequently, it was calcined at 600°C for 6 hours in a muffle furnace under a flowing air atmosphere to remove the organic structure directing agent. The product was identified as ZMQ-1 by powder X-ray diffraction, and the silicon-aluminum atomic ratio was 16.5 by ICP-OES elemental analysis.

[0090] Example 11: Molecular sieve synthesis

[0091] The synthetic gel was prepared according to the molar ratio of SiO2:0.02Al2O3:0.25Q(OH)2:0.5HF:10H2O, and the specific steps were as follows: 6 mmol of the organic structure directing agent solution described in Example 2 was weighed, 0.21 g of aluminum isopropoxide was added, and magnetic stirring was performed for 1 hour, followed by the addition of 5.21 g of tetraethyl orthosilicate, and the resulting mixture was stirred at room temperature for 12 hours. The resulting transparent gel was placed in a vacuum oven and heated at 100°C for 3 hours to remove the solvent and excess water. 0.55 mL of 48% mass concentration of HF was pipetted with a pipette gun, added to the gel, and manually stirred rapidly for 10 minutes with a plastic medicine spoon to obtain a powdered or semi-solid gel. The final synthetic gel was transferred to a 25 mL stainless steel synthesis reactor with a polytetrafluoroethylene liner and crystallized at 190°C for 5 days. The product was filtered and washed with 200 mL of water, 200 mL of ethanol, and 100 mL of acetone, and dried overnight to obtain a freshly synthesized molecular sieve. Then, the product was calcined at 600°C for 6 hours in a muffle furnace under flowing air atmosphere to remove the organic structure directing agent. The product was identified as ZMQ-1 by powder X-ray diffraction, and the silicon-aluminum atomic ratio was 18.7 by ICP-OES elemental analysis.

[0092] Example 12: Molecular sieve synthesis

[0093] The synthetic gel was prepared according to the molar ratio of SiO2: 0.02Al2O3: 0.25Q(OH)2: 0.5NH4F: 10H2O. The specific steps are as follows: 6 mmol of the organic structure directing agent solution described in Example 2 was weighed, 0.21 g of aluminum isopropoxide was added, and magnetic stirring was performed for 1 hour. Then 5.21 g of tetraethyl orthosilicate was added, and the resulting mixture was stirred at room temperature for 12 hours. The resulting transparent gel was placed in a vacuum oven and heated at 100°C for 3 hours to remove the solvent and excess water. 0.44 g of NH4F was weighed, added to the gel, and manually stirred rapidly for 10 minutes with a plastic spoon to obtain a powdered or semi-solid gel. The final synthetic gel was transferred to a 25 mL stainless steel synthesis kettle with a polytetrafluoroethylene liner and crystallized at 190°C for 5 days. The product was filtered and washed with 200 mL of water, 200 mL of ethanol, and 100 mL of acetone, and dried overnight to obtain a freshly synthesized molecular sieve. Then, the product was calcined at 600°C for 6 hours in a muffle furnace under flowing air atmosphere to remove the organic structure directing agent. The product was identified as ZMQ-1 by powder X-ray diffraction, and the silicon-aluminum atomic ratio was 19.0 by ICP-OES elemental analysis.

[0094] Example 13: Molecular sieve synthesis

[0095] The synthetic gel was prepared according to the molar ratio of SiO2:0.25Q(OH)2:0.5HF:5H2O, and the specific steps were as follows: 6 mmol of the organic structure directing agent solution described in Example 2 was weighed, 5.21 g of tetraethyl orthosilicate was added, and the resulting mixture was stirred at room temperature for 12 hours. The resulting transparent gel was placed in a vacuum oven and heated at 100°C for 3 hours to remove the solvent and excess water. 0.55 mL of 48% mass concentration of HF was pipetted with a pipette, added to the gel, and manually stirred quickly for 10 minutes with a plastic medicine spoon to obtain a powdered or semi-solid gel. The final synthetic gel was transferred to a 25 mL stainless steel synthesis kettle with a polytetrafluoroethylene liner and crystallized at 190°C for 30 days. The product was filtered and washed with 200 mL of water, 200 mL of ethanol, and 100 mL of acetone, and dried overnight to obtain a freshly synthesized molecular sieve. Subsequently, it was calcined at 600°C for 6 hours in a muffle furnace under a flowing air atmosphere to remove the organic structure directing agent. The product was identified as ZMQ-1 by powder X-ray diffraction.

[0096] Example 14: Molecular sieve synthesis

[0097] The synthetic gel was prepared according to the molar ratio of SiO2: 0.02Al2O3: 0.01TiO2: 0.25Q(OH)2: 10H2O, and the specific steps were as follows: 6 mmol of the organic structure directing agent solution described in Example 2 was weighed, 0.21 g of aluminum isopropoxide was added, magnetic stirring was performed for 1 hour, 0.086 g of tetrabutyl titanate was subsequently added, and finally 5.21 g of tetraethyl orthosilicate was added. The resulting mixture was stirred at room temperature for 12 hours, and the resulting transparent gel was placed in a vacuum oven and heated at 100°C for 3 hours to remove the solvent and excess water. The final synthetic gel was transferred to a 25 mL stainless steel synthesis reactor with a polytetrafluoroethylene liner and crystallized at 190°C for 15 days. The product was filtered and washed with 200 mL of water, 200 mL of ethanol, and 100 mL of acetone, and dried overnight to obtain a freshly synthesized zeolite molecular sieve precursor. Subsequently, it was calcined at 600°C for 6 hours in a muffle furnace under a flowing air atmosphere to remove the organic structure directing agent. The product was identified as ZMQ-1 by powder X-ray diffraction, and the silicon-titanium atomic ratio was 62 by ICP-OES elemental analysis.

[0098] Example 15: Molecular sieve synthesis

[0099] The synthetic gel was prepared according to the molar ratio of SiO2: 0.02Al2O3: 0.02TiO2: 0.25Q(OH)2: 10H2O, and the specific steps were as follows: 6 mmol of the organic structure directing agent solution described in Example 2 was weighed, 0.21 g of aluminum isopropoxide was added, magnetic stirring was performed for 1 hour, 0.17 g of tetrabutyl titanate was subsequently added, and finally 5.21 g of tetraethyl orthosilicate was added. The resulting mixture was stirred at room temperature for 12 hours, and the resulting transparent gel was placed in a vacuum oven and heated at 100°C for 3 hours to remove the solvent and excess water. The final synthetic gel was transferred to a 25 mL stainless steel synthesis kettle with a polytetrafluoroethylene liner and crystallized at 190°C for 10 days. The product was filtered and washed with 200 mL of water, 200 mL of ethanol, and 100 mL of acetone, and dried overnight to obtain a freshly synthesized zeolite molecular sieve precursor. Subsequently, it was calcined at 600°C for 6 hours in a muffle furnace under a flowing air atmosphere to remove the organic structure directing agent. The product was identified as ZMQ-1 by powder X-ray diffraction, and the atomic ratio of silicon to titanium was 15 by ICP-OES elemental analysis.

[0100] For the calcined molecular sieve ZMQ-1 obtained in each of the above examples, continuous rotating electron diffraction (cRED) was used to obtain three-dimensional diffraction data and perform structural analysis. The results show that the structure of the ZMQ-1 molecular sieve has orthogonal symmetry and is a Cmmm space group. The unit cell parameters after refinement are:

[0101] and

[0102] The results of topological analysis show that the framework structure of ZMQ-1 zeolite contains 18 topologically independent T atoms. More specific topological features are shown in Table 2.

[0103] Table 2.

[0104]

[0105]

[0106] The powder X-ray diffraction spectrum of the zeolite molecular sieve synthesized in Example 3-5 is as follows: Figure 1 As shown, both the freshly synthesized and calcined products gave clear and unique characteristic diffraction peaks. The diffraction peaks of the samples calcined at 600°C and 800°C determined that the phase was ZMQ-1 molecular sieve, confirming its high thermal stability. Figure 2 The X-ray diffraction peaks of the product after treatment with 50% water vapor are given, all of which are ZMQ-1 molecular sieve, proving that the aluminosilicate molecular sieve has high hydrothermal stability. Figure 3 The X-ray diffraction spectra of ZMQ-1 molecular sieves with different Ti contents synthesized in Examples 14 and 15 are given. The argon physical adsorption data of the calcined zeolite molecular sieves confirm that the molecular sieves have a high micropore adsorption capacity, containing mesopores and ultra-large micropores, such as Figure 4 As shown; the crystallographic aperture size is as Figure 5 shown. Figure 6 and Figure 7 The scanning electron microscope and transmission electron microscope photos of the samples calcined at 600° C. in Example 3 and Example 11 respectively, the grains all have a quadrangular prism morphology. Figure 8 The skeleton (A, B, DF) and high-resolution transmission electron microscope atomic image (C) of the molecular sieve calcined at 600°C in Example 3 show the 28-membered ring channels along the c-axis and the 10-membered ring channels of different sizes along the a and b-axis directions.

Claims

1. A silicate zeolite molecular sieve precursor, characterized in that: The anhydrous chemical composition of the silicate zeolite molecular sieve precursor is SiO2·1 / xXO 1.5 mMO 0.5 qQ, where X is a framework trivalent element, Si / X molar ratio x≥5, M is a framework balancing cation, M / Si molar ratio 0≤m≤1, Q is a diquaternary phosphorus organic structure directing agent, Q / Si molar ratio q≥0.01; The X-ray diffraction characteristics of the silicate zeolite molecular sieve precursor powder are as follows:

2. A silicate zeolite molecular sieve, characterized in that: The anhydrous chemical composition of silicate zeolite molecular sieve is SiO2·1 / xXO 1.5 mMO 0.5 , wherein X is a framework trivalent element, the Si / X molar ratio x≥5, M is a framework balancing cation, and the M / Si molar ratio 0≤m≤1; The silicate zeolite molecular sieve contains a three-dimensional pore system consisting of 28×10×10 rings, wherein the size of the 28-membered ring is The sizes of the 10-membered ring are and The silicate zeolite molecular sieve is obtained by calcining the silicate zeolite molecular sieve precursor according to claim 1.

3. The silicate zeolite molecular sieve according to claim 2, characterized in that: The silicate zeolite molecular sieve has the powder X-ray diffraction characteristics shown in the following table:

4. The silicate zeolite molecular sieve according to claim 2, characterized in that: The molecular sieve has an orthorhombic crystal structure, a space group of Cmmm (No. 65), and unit cell parameters of: and And, it has the topological characteristics shown in the following table:

5. The molecular sieve according to claim 2, characterized in that: The framework trivalent element X is selected from at least one of boron, aluminum, gallium, indium, iron and chromium; the framework balanced cation M is selected from at least one of hydrogen ion, ammonium ion, lithium ion, sodium ion, potassium ion, rubidium ion, cesium ion, etc.; the molecular sieve contains a non-silicon tetravalent framework element Y with a mass greater than 0 and less than or equal to 10w%, wherein Y is selected from at least one of germanium, tin, titanium, zirconium and hafnium; silicon in the precursor or molecular sieve can be partially replaced by at least one of germanium, tin, titanium, zirconium and hafnium; other framework divalent elements Z can be introduced into the molecular sieve, wherein Z is selected from at least one of zinc, beryllium, copper, cobalt, iron, manganese, chromium, molybdenum and tungsten, and the molar ratio of divalent elements to silicon is greater than 0 and less than or equal to 0.

1.

6. A method for preparing the silicate zeolite molecular sieve according to claim 2, characterized in that: A framework balanced cationic compound, a silicon source, a framework trivalent element X source, an organic structure directing agent and a reagent are mixed to obtain a synthetic gel; the synthetic gel is then aged and hydrothermally crystallized, and the crystallized product is roasted to remove the organic structure directing agent; wherein the molar ratio of the synthetic gel after aging is SiO2:mM2O:xX2O3:qQ(OH)2:hH2O, wherein M is a framework balanced cation, X is a framework trivalent element, and Q is a cationic group of the organic structure directing agent, and the value ranges of m, x, q and h are: m=0-1, x=0-0.5, q=0.1-1, and h=3-100; The reagent is water and / or a fluorine-containing mineralizer; The organic structure directing agent has the following configuration: Wherein, Q is phosphorus, R1, R2, R3, R4, R5, R6 may be the same or different and selected from cyclohexyl or phenyl, R7 and R8 are H or methyl, and n is 0-8.

7. A molecular sieve composition, characterized in that: The composition contains the silicate zeolite molecular sieve precursor according to claim 1 and / or the silicate zeolite molecular sieve according to claim 2.

8. An application of the silicate zeolite molecular sieve according to claim 2, characterized in that: The use of the silicate zeolite molecular sieve according to claim 2 or the molecular sieve composition according to claim 7 as an energy storage material, chemical sensing material, carrier, adsorbent, separation agent or catalyst.

Citation Information

Patent Citations

  • Super-macroporous silicate molecular sieve ZEO-1 as well as synthesis method and application thereof

    CN114538466A

  • Silicate material ZEO-2, silicate molecular sieve ZEO-3, synthesis method and application thereof

    CN115611293A

  • Zeolite synthesis using biquaternary ammonium structure directing agents

    CN114364637A

Cited By

  • Modified molecular sieve for co-catalytic pyrolysis of cellulose and waste plastics and application of modified molecular sieve

    CN120861133A